Cadmium and Zinc Concentration in Grain of Durum Wheat in Relation to Phosphorus Fertilization, Crop Sequence and Tillage Management - Xiaopeng Gao; Cynthia A. Grant (Applied and Environmental Soil Science)
Field experiments were conducted at two locations in Manitoba, Canada, to determine the effect of crop rotation, phosphorus (P) fertilization and tillage on grain yield and grain concentrations of Cd and Zn in durum wheat (Triticum durum L.). Compared to conventional tillage (CT), reduced tillage (RT) management decreased grain Cd and increased grain yield and grain Zn in half of the site-years. The type of preceding crops of spring wheat-flax or canola-flax had little influence. Rate and timing of P application had little effect on grain Cd, but increasing P rate tended to decrease grain Zn. No interactive effect was detected among tested factors. Grain Zn was not related to grain Cd, but positively to other nutrients such as Fe, Mn, P, Ca, K, and Mg. Both grain Zn and Fe correlated positively with grain protein content, suggesting protein may represent a sink for micronutrients. The study suggested that the tillage management may have beneficial effects on both grain yield and quality. Phosphorus fertilizer can remain available for subsequent crops and high annual inputs in the crop sequence may decrease crop grain Zn. Understanding the environment is important in determining the impact of agricultural management on agronomic and nutrient traits.